Bir, İki ve Üç Boyutlu Helyum-4 (He-4) Atomunun Termodinamik Özellikleri - SHEHADEH, YOUSEF HUSSEIN ABED (İstanbul Kültür Üniversitesi, 2023)
Bu tez kapsamında, aynı gaz molekülleri arasındaki etkileşimleri belirlemek için (2He4) gazının termodinamik özellikleri, hal denkleminde (2He4) için ikinci virial katsayıya, iki farklı, atomlar arası.etkileşme potansiyeli uygulanarak incelenmiştir. Sonuç olarak, verilen bir sıcaklıkta klasik virial katsayısı ve kuantum düzeltme virial katsayısında temsil edilen birçok özellik hesaplanmıştır. İkinci virial katsayı için, farklı potansiyellerden türetilen basit bir yaklaşık analitik ifade türetilmiştir.

In this thesis, in order to determine interactions between the same gas molecules, the thermodynamic properties of (2He4) gas have been investigated, using the equation of state, where two different interatomic interaction potentials for (2He4) on the second virial coefficient were applied. As a result, many properties, represented in classical virial coefficient and quantum correction virial coefficient at a given temperature, were calculated. A simple approximate analytical expression for the second virial coefficient was derived from different potentials.
▪ Yüksek lisans tezi.
Keywords: Helyum